A Diffusion Model to Quantify Membrane Repair Process in Listeria monocytogenes Exposed to High Pressure Processing Based on Fluorescence Microscopy Data - Nikparvar, Bahareh; Subires, Alicia; Capellas, Marta; Hernandez-Herrero, Manuela; Crauwels, Peter; Riedel, Christian U.; Bar, Nadav (Frontiers in Microbiology, 2021)
The effects of environmental stresses on microorganisms have been well studied, and cellular responses to stresses such as heat, cold, acids, and salts have been extensively discussed. Although high pressure processing (HPP) is becoming more popular as a preservation method in the food industry, the characteristics of the cellular damage caused by high pressure are unclear, and the microbial response to this stress has not yet been well explored. We exposed the pathogen Listeria monocytogenes to HPP (400 MPa, 8 min, 8◦C) and found that the high pressure created plasma membrane pores. Using a common staining technique involving propidium iodide (PI) combined with high-frequency fluorescence microscopy, we monitored the rate of diffusion of PI molecules into hundreds of bacterial cells through these pores on days 0, 1, 2, 3, and 4 after pressurization. We also developed a mathematical dynamic model based on mass transfer and passive diffusion laws, calibrated using our microscopy experiments, to evaluate the response of bacteria to HPP. We found that the rate of diffusion of PI into the cells decreased over the 4 consecutive days after exposure to HPP, indicating repair of the pressure-created membrane pores. The model suggested a temporal change in the size of pores until closure. To the best of our knowledge, this is the first time that pressure-created membrane pores have been quantitatively described and shown to diminish with time. In addition, we found that the membrane repair rate in response to HPP was linear, and growth was temporarily arrested at the population level during the repair period. These results support the existence of a progressive repair process in some of the cells that take up PI, which can therefore be considered as being sub-lethally injured rather than dead. Hence, we showed that a subgroup of bacteria survived HPP and actively repaired their membrane pores.